2007
DOI: 10.5713/ajas.2007.1305
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Methane Production from Ruminants

Abstract: On a global scale agriculture and in particular enteric fermentation in ruminants is reported to produce about one fourth (21 to 25%) of the total anthropogenic emissions of methane (CH 4 ). Methane is produced during the anaerobic fermentation of hydrolyzed dietary carbohydrates in the rumen and represents an energy loss to the host besides contributing to emissions of greenhouse gases into the environment. However, there appears to be uncertainty in the CH 4 estimation from livestock due to the limited avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 74 publications
0
49
0
1
Order By: Relevance
“…Penurunan populasi keduanya dapat menurunkan pemakaian gas CO2 yang digunakan sebagai komponen pembentukan gas metana. Bhatta et al (2007) menjelaskan bahwa komponen utama proses metanogenesis pada ruminansia adalah ion hidrogen dan CO2.…”
Section: Karakteristik Produksi Gasunclassified
“…Penurunan populasi keduanya dapat menurunkan pemakaian gas CO2 yang digunakan sebagai komponen pembentukan gas metana. Bhatta et al (2007) menjelaskan bahwa komponen utama proses metanogenesis pada ruminansia adalah ion hidrogen dan CO2.…”
Section: Karakteristik Produksi Gasunclassified
“…However, Bhatta et al (2007) compared the various approaches and showed that the RUSITEC semi continuous culture approach gave consistently lower methane data that the SF6 technique regardless of diet. The batch culture approach gave vary variable data compared to SF6 after 24 hrs of incubation but consistently higher after 48 hrs.…”
Section: 33mentioning
confidence: 99%
“…Substrates for ruminal methanogenesis are derived from dietary carbohydrates (cellulose, hemi-cellulose, pectin and starch). When these substrates are hydrolyzed, hydrogen and carbon dioxide are produced, which due to metabolism by methanogens yield methane (Bhatta et al, 2007). Maize stover C o m b i n a t i o n o f c e l l u l a s exylanase--D-glucanase 25,600-25,600-0 IU/g C e l l u l a s e -x y l a n a s e --Dglucanase 12,800-12,800-0 IU/g…”
Section: Mitigating Methane Emissionmentioning
confidence: 99%
“…As known for many years, fermentation of dietary carbohydrates in the rumen by methanogenic archaea produces methane gas. Methane production tends to increase as the fiber content of feed increases (Kurihara et al, 2007). Type of carbohydrate of agricultural by-product, especially fodder/straw, contains high level of fiber.…”
Section: Introductionmentioning
confidence: 99%